Selective ablation of P53 in pancreatic beta cells fails to ameliorate glucose metabolism in genetic, dietary and pharmacological models of diabetes mellitus - Celina Uhlemeyer; Nadine Müller; Michael Rieck; Jennifer Kuboth; Caroline Schlegel; Kerstin Grieß; Tim Florian Dorweiler; Sonja Heiduschka; Jürgen Eckel; Michael Roden; Eckhard Lammert; Markus Stoffel; et al. (Molecular Metabolism, 2023)
Objective: Beta cell dysfunction and death are critical steps in the development of both type 1 and type 2 diabetes (T1D and T2D), but the underlying mechanisms are incompletely understood. Activation of the essential tumor suppressor and transcription factor P53 (also known as TP53 and Trp53 in mice) was linked to beta cell death in vitro and has been reported in several diabetes mouse models and beta cells of humans with T2D. In this article, we set out to determine the beta cell specific role of P53 in beta cell dysfunction, cell death and development of diabetes in vivo. Methods: We generated beta cell specific P53 knockout (P53BKO) mice and used complementary genetic, dietary and pharmacological models of glucose intolerance, beta cell dysfunction and diabetes development to evaluate the functional role of P53 selectively in beta cells. We further analyzed the effect of P53 ablation on beta cell survival in isolated pancreatic islets exposed to diabetogenic stress inducers ex vivo by flow cytometry. Results: Beta cell specific ablation of P53/Trp53 failed to ameliorate glucose tolerance, insulin secretion or to increase beta cell numbers in genetic, dietary and pharmacological models of diabetes. Additionally, loss of P53 in beta cells did not protect against streptozotocin (STZ) induced hyperglycemia and beta cell death, although STZ-induced activation of classical pro-apoptotic P53 target genes was significantly reduced in P53BKO mice. In contrast, Olaparib mediated PARP1 inhibition protected against acute ex vivo STZ-induced beta cell death and islet destruction. Conclusions: Our study reveals that ablation of P53 specifically in beta cells is unexpectedly unable to attenuate beta cell failure and death in vivo and ex vivo. While during development and progression of diabetes, P53 and P53-regulated pathways are activated, our study suggests that P53 signaling is not essential for loss of beta cells or beta cell dysfunction. P53 in other cell types and organs may predominantly regulate systemic glucose homeostasis.